Extratemporal disconnective procedures for the treatment of epilepsy in children. (April 2017) - Santos, Marcelo Volpon; Machado, Hélio Rubens
Summary: Surgical treatment of epilepsy in children often involves brain areas outside the temporal lobe and, therefore, techniques for extratemporal surgery must be included in the armamentarium of epilepsy surgery centers. Nowadays, disconnective procedures are preferable to traditional resective operations because they reduce the rate of complications related to extensive resections while achieving equivalent seizure outcomes. This article describes the practical anatomy and surgical techniques used for temporoparietooccipital (TPO), parietooccipital, and frontal disconnections, as well as the possibility of extending previous lobar disconnections to the whole hemisphere (hemispherotomy).